The nuclear pore complex prevents sister chromatid recombination during replicative senescence - Paula Aguilera (Nature Portfolio, 2020)
The Nuclear Pore Complex has been linked to DNA damage processing. Here the authors reveal that the Nup1 C-terminus is critical for the relocalization of eroded telomeres to nuclear pores and that modification of Nup1 promotes sister chromatid recombination and unleashes a new telomere maintenance mechanism.